In vivo characterization of a luffa-based composite scaffold for subcutaneous implantation in rats - Gundu S.; Sahi A.K.; Kumari P.; Tekam C.S.; Allu I.; Singh R.; Mahto S.K. (My University, 2025)
Recent advancements in tissue engineering have witnessed luffa-derived scaffolds, exhibiting their exceptional potential in cellular proliferation, biocompatibility, appropriate interconnectivity, and biomechanical strength. In vivo studies involved implanting fabricated scaffolds subcutaneously in Wistar rats to evaluate their impact on the heart, liver, and kidneys. This approach provided a safe and minimally invasive means to evaluate scaffold compatibility with surrounding tissues. Male Wistar rats were categorized into four distinct groups, Group A, B, C, and D are referred to as 3% LC implanted scaffolds, 5% LC implanted scaffolds, control (without luffa scaffolds), and Sham (without any scaffold implantation), respectively. Histological analysis in all the groups indicated that the animal models did not exhibit any signs of inflammation or toxicity, suggesting favorable tissue response to the implanted scaffolds. Initial observations revealed elevated levels of enzymes and biomarkers in the experimental groups after a 24 h interval, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), bilirubin, creatine kinase-MB (CK-MB), and serum creatinine. However, these parameters normalized 3 weeks post-implantation, with no significant increase compared to the control groups, suggesting that the implanted luffa-based scaffolds did not induce adverse effects on the heart, liver, and kidneys. Furthermore, the scaffold’s significant pore size and porosity enable it to release drugs, including antibacterial medications. This study demonstrates promising results, indicating excellent scaffold porosity, sustained drug release, affirming the in vivo biocompatibility, absence of inflammatory responses, and overall tissue compatibility highlighting the immense potential of these luffa-based scaffolds in various tissue engineering and regenerative medicine applications. © 2024 Informa UK Limited, trading as Taylor & Francis Group.